The Implementation of Google Chromebook Media to Enhance Students' Learning Interest in Islamic Religious Education Subject in Grade VI at UPTD SPF SDN 205 Macanre - Rahmawati. R (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This research presents a study on the implementation of digital learning media, specifically the use of Google Chromebook, in the Islamic Religious Education (PAI) subject at SDN 205 Macanre, Soppeng Regency. The research focuses on two core aspects: (1) the use of Google Chromebook as a learning medium and (2) students' learning interest. A qualitative approach with a case study method was employed in this research. Data were collected through observation, in-depth interviews, and documentation, and analyzed using content analysis techniques. A theological approach was also utilized to examine how the implementation of Google Chromebook aligns with the pedagogical goals of Islamic education in the studied context. The findings indicate that the integration of Google Chromebook into PAI learning contributes positively to the effectiveness of the teaching and learning process, particularly in terms of increasing students' motivation, participation, and comprehension of Islamic values. Nevertheless, the success of this implementation is largely dependent on systemic readiness, teacher digital competence, and continuous institutional support in developing an inclusive and sustainable digital learning ecosystem. Furthermore, students' interest in learning PAI is significantly influenced by innovative, interactive, and personally relevant teaching approaches. When students perceive that the learning content is engaging, meaningful, and compatible with their learning styles, their intrinsic motivation and interest naturally increase.